2020
DOI: 10.3892/or.2020.7615
|View full text |Cite
|
Sign up to set email alerts
|

Girdin interaction with vimentin induces EMT and promotes the growth and metastasis of pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant cancer of the digestive tract that has a high potential for metastasis and a poor prognosis. Girdin was first reported in 2005 as an actin-binding protein and was designated as Akt-phosphorylation enhancer (APE); thus, Girdin has been revealed to have an important role in regulating cancer development. There is additional evidence indicating that Girdin is associated with cell proliferation, migration, invasion and survival in certain cancers. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Tu et al (13) and Lee et al (35), reported that FBLN5 was involved in EMT and affected the invasion and migration by tumor-associated MMPs in breast cancer and hepatocellular carcinoma cells. EMT is a cellular process and is often defined as the loss of epithelial characteristics and the increase in mesenchymal features (36,37). Consistent with this hypothesis, the results in the present study revealed that FBLN5 overexpression increased the epithelial marker, E-cadherin and decreased the mesenchymal markers, N-cadherin and Snail.…”
Section: Discussionsupporting
confidence: 90%
“…Tu et al (13) and Lee et al (35), reported that FBLN5 was involved in EMT and affected the invasion and migration by tumor-associated MMPs in breast cancer and hepatocellular carcinoma cells. EMT is a cellular process and is often defined as the loss of epithelial characteristics and the increase in mesenchymal features (36,37). Consistent with this hypothesis, the results in the present study revealed that FBLN5 overexpression increased the epithelial marker, E-cadherin and decreased the mesenchymal markers, N-cadherin and Snail.…”
Section: Discussionsupporting
confidence: 90%
“…[ 18 ] Another actin regulatory protein, girdin, that links protein kinase B (AKT) signaling to cytoskeletal dynamics was shown to bind vimentin by mass spectrometry and immunoprecipitation from pancreatic cancer cells. [ 19 ] Hic‐5, a focal adhesion scaffold protein stabilizes the VIF network by modulation of RhoGTPases, and its ablation leads to the disassembly of VIF. [ 20 ] Filamin A, an actin crosslinker, directs the kinase PAK1 to vimentin, altering its assembly into VIFs.…”
Section: Vimentin Binds To Diverse Cellular Targetsmentioning
confidence: 99%
“…These results suggest that the proproliferation and anti-apoptotic functions of KLK8 may not be dependent on activation of Notch signaling pathway. Notably, our GSEA analysis data showed that KLK8 overexpression might also lead to the activation of EMT (epithelial-mesenchymal transition), glycolysis and KRAS signaling pathway, which have been implicated in the pathogenesis and progression of pancreatic cancers [17,[43][44][45]. Whether these processes and the related signaling pathways contribute to the KLK8-induced pro-proliferation and anti-apoptotic effects in pancreatic cancers merits further investigation.…”
Section: Discussionmentioning
confidence: 84%